Electrophysiological predictors of response to subcutaneous immunoglobulin therapy in chronic inflammatory demyelinating polyneuropathy. Issue 9 (September 2021) - Alcantara, Monica; Hartung, Hans-Peter; Lawo, John-Philip; Durn, Billie L.; Mielke, Orell; Bril, Vera
Highlights: Relapse and axonal damage were analyzed in the PATH study of subcutaneous immunoglobulin (IgPro20) in CIDP. On placebo, non-axonal damage patients relapsed more than axonal damage patients. IgPro20 was less effective in patients with axonal damage than those without. Abstract: Objective: To assess axonal function prior to subcutaneous immunoglobulin (SCIG) therapy or placebo in relation to relapse in chronic inflammatory demyelinating polyneuropathy (CIDP) to determine whether axonal damage can predict therapy response. Methods: Relapse rates in patients from the Polyneuropathy and Treatment with Hizentra (PATH) study, where patients were treated with placebo or SCIG (IgPro20), were analyzed by baseline (post-intravenous immunoglobulin stabilization) axonal damage (≤1 mV peroneal compound muscle action potential) status. Results: In patients with non-axonal damage, relapses were significantly higher with placebo (73.0%) than IgPro20 (0.2 g/kg: 39.1%, 0.4 g/kg: 19.2%). In patients with axonal damage, IgPro20 had no effect on relapse (placebo: 25.0%, IgPro20: 0.2 g/kg: 30.0%, 0.4 g/kg: 19.4%). Patients with axonal damage relapsed significantly less on placebo versus non-axonal damage, but they also demonstrated higher baseline disability. Conclusion: Axonal damage may correspond to relapse upon treatment withdrawal; patients with axonal damage relapse less, possibly reflecting poor response to immunoglobulin therapy, while non-axonal damage patients may experience more relapse, perhaps indicating better treatment response. Significance: In CIDP patients with axonal loss, immunoglobulin therapy may not be as effective. Assessing axonal damage could help guide therapy, with immunoglobulins ideally used before substantial axonal damage arises.